Observation and properties of the X(3872) decaying to J/ψπ+π- in pp̄ collisions at √s = 1.96 TeV - Abazov, V. M. (2004)
The discovery of a new particle, X(3872) by the Belle collaboration in the decay mode B±→ XK± (X→ J/ψπ+π - was discussed. It was found that the mass of the X(3872) was measured to be 3872.0 ± 0.6(stat) ± 0.5 (syst) MeV/C2. The X(3872) particle were observed in approximately 230 pb-1 of data with a significance of 5.2 standard deviations. The results show that there was no significant differences between the X(3872) and the cc̄ state ψ (2S).